2018
DOI: 10.18203/2320-1770.ijrcog20180195
|View full text |Cite
|
Sign up to set email alerts
|

Labour with low dose epidural analgesia: maternal perception and fetal outcome

Abstract: Background: Experiencing labour pains and giving birth to infant is normal physiological process. Though it is a natural phenomenon, it produces severe pain which requires analgesia to relieve pain during labour. The objective of this study was to compare effects of low dose epidural analgesia verses no analgesia during labour on mother and fetus. Methods: Here in this study we have assessed effect of epidural analgesia on mother and fetus. Total we have taken 60 women in age group of 20-26 years with full ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
5
1
Order By: Relevance
“…(Gp. B) supported by Vasudha et al [8] & Agarwal D et al [4]. In current study, the second stage was found to be prolonged in epidural group as compared to control.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…(Gp. B) supported by Vasudha et al [8] & Agarwal D et al [4]. In current study, the second stage was found to be prolonged in epidural group as compared to control.…”
Section: Discussionsupporting
confidence: 74%
“…There was statistically significant difference in mean duration of first stage of labor in both groups with p value of <0.05 which is statistically significant, as opposed to study by Wong FM et al [3] & Vasudha et al [8]. Second stage of labor was slightly prolonged in Epidural gp.…”
Section: Discussioncontrasting
confidence: 63%
“…It could be explained by the fact that the epinephrine levels are reduced by epidural analgesia resulting in decreased adrenergic receptor stimulation leading to enhanced uterine perfusion and more effective contraction. [ 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Sawant V Kumbhar A. concluded Epidural analgesia appears to have significant pain relief as compared to no analgesia during labour. 33…”
Section: Pain Reliefmentioning
confidence: 99%